High Harmonic Generation by Bright Squeezed Vacuum - Rasputnyi, Andrei; Birk, Michael; Chen, Zhaopin; Cohen, Oren; Krüger, Michael; Kaminer, Ido; Chekhova, Maria; Tani, Francesco (CLEO: Fundamental Science, CLEO:FS 2024 in Proceedings CLEO 2024 - Part of Conference on Lasers and Electro-Optics, 2024)
We present the first observation of non-perturbative high-harmonic generation driven by nonclassical light, namely bright squeezed vacuum. Compared to classical light, bright squeezed vacuum leads to higher efficiency, different power scaling, and unique photon-number distributions.
CRIS-Team Scopus Importer:2024-10-25